ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PENGRAJIN GENTENG PRESS MINI DI DESA PEJATEN KECAMATAN KEDIRI KABUPATEN TABANAN - I DEWA GEDE RASTANA; I NYOMAN ARIANA GUNA; I WAYAN MULA SARJANA (Jurnal Ilmiah Satyagraha, 2023)
The role of the small industry sector for mini press tile crafts in PejatenVillage, Kediri District, is expected to be able to contribute to regional economicgrowth and the development of the industrial sector, especially the mini press tileindustry which can increase the income of the craftsmen, is one of the factors thatplay a role in absorption labor. The formulation of the problem in this study,whether the amount of production, labor, and working hours have a partial orsimultaneous effect on income in the mini press tile craftsman industry, PejatenVillage, Tabanan Regency.The research sample was taken from all populations with the saturated samplemethod ,because the sampling of the population was carried out as a whole fromthe existing population as mini press tile entrepreneurs. The number of samplesthat were determined was the entire population of 35 entrepreneurs spread overseveral banjars in Pejaten Village, Kediri District, Tabanan Regency. The dataanalysis technique used is multiple linear regression analysis technique.Based on the results of the study, it can be explained that: (1) The amountof production has a real and positive effect on income in the mini press tileindustry in Pejaten Village, Kediri District, because the tcount is greater than ttable or6.789 > 1.695 and the significance value is smaller. Of 5% or 0.000 < 0.05. (2)Labor has a real and positive influence on income in the mini press tile industry inPejaten Village, Kediri District, because the tcount is greater than ttable or 2,095 >1,695 and the significance value is less than 5% or 0,044 < 0,05 . (3) Workinghours have a significant and positive effect on the value of income in the minipress tile industry in Pejaten Village, Kediri District, because the tcount is greaterthan ttable or 2,056 > 1,695 or the significance is less than 5% or 0,038 < 0,05 . (4)The amount of production (X1), labor (X2), and working hours (X3) together havea real and positive influence on income in the mini press tile industry in PejatenVillage, Kediri District, this can be seen from the value of the Fratio is greater thanthe Ftable or 37.453 > 2.910. Likewise, when viewed from the significance value,which is 0.000, it is smaller than 0.05 (5%) or 0.000 <0.05. Based on the results ofthe analysis of determination, the percentage of the contribution of the influence of the independent variable (amount of production, labor and working hours) onthe dependent variable (income) of 78.4%. While the remaining 21.6% isinfluenced or explained by other variables that are not included in this researchmodel.